The implementation of a measurement system for brushless DC motor parameters. Issue 12 (26th September 2017) - Ho, Tze-Yee; Liu, Fang-Ta; Ho, Guan-Wei; Lin, Yan-Ru
ABSTRACT: Most of the energy conversion in industrial devices and equipment is completed by the motor. The acquirement of motor parameters becomes very important for designing the motor drives. The aim of this paper is to design and implement a motor measurement system. Through the processing of an Advanced RISC Machines (ARM) microcontroller, the various parameters of motors such as input voltage, input current, input power, motor speed, and motor torque can be obtained. Consequently, the torque constant, load torque, viscous friction, and the inertia of the motor are calculated and achieved. The motor parameters can be commanded and displayed in the designed human interface of a PC via USB communication. The hardware system designed in this system includes an ARM microcontroller, an inverter, a voltage sensor, a current sensor, a torque sensor, and power supply. The software programming is developed under the Visual Studio 2012 environment development platform using the C language. Finally, the prototype of the motor measurement system is completed and verified. The experimental results for the motor parameters and torque/speed characteristic are demonstrated and show the feasibility of the complete designed system.